“Me gritaron Negra”: entre la negación y la reivindicación (Tema Central) - Gordillo Íñiguez, Sandra Katherine (2020)
In the poem “They shouted at me Black” from the Peruvian Victoria Santa Cruz, the word becomes a bridge that unites denial and claim. This article analyzes this conjunction with legal lens, to do so the poem is broken down, linking each part with different categories: the other, racism and discrimination, identity, black feminism and intersectionality. In addition, the explicit literary figures in the poem and their implicit claim burden are reviewed. Finally, the relevance of the word black within the poem is studied through an analysis of the polarity of feelings, an analysis of the frequency of words and their corresponding interpretation. Between the lines, the poem whispers to us that the negative social significance of the black has been constructed from the pedestal of the normal ones, sustained by the passive acceptance of the oppressed, and legitimized from the state political-legal structure.